Core–shell FePt-cube@covalent organic polymer nanocomposites: a multifunctional nanocatalytic agent for primary and metastatic tumor treatment. Issue 48 (16th November 2020) - Meng, Yanfei; Zhang, Dongsheng; Sun, Yunqiang; Dai, Zhichao; Zhang, Tiantian; Yu, Dexin; Zhang, Gaorui; Zheng, Xiuwen
Abstract : Metastasis and spread are currently the main factors leading to high mortality of cancer, so developing a synergetic antitumor strategy with high specificity and hypotoxicity is in urgent demand. Abstract : Metastasis and spread are currently the main factors leading to high mortality of cancer, so developing a synergetic antitumor strategy with high specificity and hypotoxicity is in urgent demand. Based on the design concept of "nanocatalytic medicine", multifunctional nanotherapeutic agent FePt@COP-FA nanocomposites (FPCF NCs) are developed for cancer treatment. Specifically, in the tumor microenvironment (TME), FePt could catalyze intracellular over-expressed H2 O2 to generate highly active hydroxyl radicals (˙OH), which could not only induce the apoptosis of tumor cells, but also activate the "ferroptosis" pathway resulting in the lipid peroxide accumulation and ferroptotic cell death. Moreover, owing to the excellent photothermal effect, the FPCF NCs could effectively ablate primary tumors under near-infrared (NIR) laser irradiation and produce numerous tumor-associated antigens in situ . With the assistance of a checkpoint blockade inhibitor, anti-CTLA4 antibody, the body's specific immune response would be initiated to inhibit the growth of metastatic tumors. In particular, such synergistic therapeutics could produce an effective immunological memory effect, which could prevent tumor metastasis and recurrence again. In summary, the FPCF NC is an effective multifunctional antitumor therapeutic agent for nanocatalytic/photothermal/checkpoint blockade combination therapy, which exhibits great potential in nanocatalytic anticancer therapeutic applications.